DOI: 10.14264/b5e42cc
|View full text |Cite
|
Sign up to set email alerts
|

UQ eSpace

Abstract: Summarises the purpose, identifies considerations and findings made in the final report to allow other personal to attain a terse summary of overall project, including key aims, processes, results and final recommendations. Professional Development Analysis Critical review of professional development, areas of potential improvement, project feedback, and identification of how development can be applied as part of future professional practice. Engineers Australia level 1 competencies used as part of this proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The epithelium forms distinct sites for the attachment of symbiotic microorganisms [26]. The termite hindgut was assumed to be anaerobic [27][28][29][30][31][32][33][34], while Eutick et al [35] suggested it to be microaerophilic. Kuhnigk et al [34] isolated also aerobic bacteria from the hindgut and found that aromatic compounds are only degraded with oxygen by the hindgut flora, which indicates a constant diffusion of oxygen through the paunch epithelium.…”
Section: Anatomy and Chemistry Of The Termite Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…The epithelium forms distinct sites for the attachment of symbiotic microorganisms [26]. The termite hindgut was assumed to be anaerobic [27][28][29][30][31][32][33][34], while Eutick et al [35] suggested it to be microaerophilic. Kuhnigk et al [34] isolated also aerobic bacteria from the hindgut and found that aromatic compounds are only degraded with oxygen by the hindgut flora, which indicates a constant diffusion of oxygen through the paunch epithelium.…”
Section: Anatomy and Chemistry Of The Termite Gutmentioning
confidence: 99%
“…The oxygen is readily used by aerobic and facultatively anaerobic microorganisms and, therefore, the gut contents remain anaerobic. Using redox dye feeding technique, several authors have measured the redox state of the gut of termites [31,32,34]. The fore-and midgut of all species were aerobic with an E~, in excess of + 100 mV.…”
Section: Anatomy and Chemistry Of The Termite Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation was followed more recently by a Queensland court in Veivers v Connolly. 15 In the "statutory jurisdictions" -the Australian Capital Territory, the Northern Territory, South Australia, Tasmania and Western Australia -parliaments rather than courts have implemented change to abortion laws (see the ]). In the ACT, there are no criminal abortion provisions, but abortions must be carried out by medical practitioners in approved clinics.…”
Section: Current Lawmentioning
confidence: 99%